The Level of Pedestrian Safety Among Rural and Urban School Children - Ibrahim, Norul Najwa; Ab. Ghani, Ahmad Raqib (Recent Trends in Civil Engineering and Built Environment, 2021)
This study aims to examine the level of pedestrian safety among students in schools at urban and rural area. The study area involved two selected schools located in the Kota Bharu to represent urban area and rural area. The number of samples used was 300 involving students who walk to school. The data used was of primary and secondary sources. The primary data was collected by means of questionnaires, observations and interview sessions with respondents. Meanwhile, secondary data was obtained by means of library research, reports and journals from electronic sources. The data was analysed using descriptive and inferential statistics. Descriptive analyses were presented in the form of percentages, frequencies, means and standard deviations. The results showed that traffic congestion factor was the biggest risk leading to road traffic accidents in both urban and rural school areas. Next, the overall findings showed that the level of respondents’ satisfaction towards the four variables tested namely facilities, environment, traffic and attitudes were still at unsatisfactory level. For comparative test, the results showed that the level of pedestrian safety among school students in rural areas was better compared to urban areas.